Late atrial arrhythmias after lung transplantation: a meta-analysis. Issue 8 (August 2020) - Saglietto, Andrea; Matta, Mario; Gaita, Fiorenzo; De Ferrari, Gaetano M.; Anselmino, Matteo
Abstract : Background: Atrial arrhythmias are common following noncardiac thoracic surgery. In particular, early postoperative atrial arrhythmias after lung transplantation are very frequent, especially atrial fibrillation (AFib). Late atrial arrhythmia occurrence following lung transplantation, instead, has been less commonly reported. Methods: The aim of the present systematic review and meta-analysis is to analyse the incidence rate of late atrial arrhythmia and AFib in lung transplantation patients, with a special focus on double lung transplant (DLT), also to assess potential predictors of AFib occurrence. After bibliographic search (PUBMED/Medline and Embase databases), a random-effect model meta-analysis was performed: seven studies were finally included, including 2068 lung transplantation patients. Results: The pooled incidence rate of late atrial arrhythmia was 4.3%/year [95% confidence interval (CI) 2.8–6.1%/year, I 2 = 69%], whereas late AFib incidence rate was 1.5%/year (95% CI 0.7–2.6%/year, I 2 = 87%). In patients undergoing DLT, the pooled incidence rate of late atrial arrhythmia was 4.1%/year (95% CI 2.5–6.0%/year, I 2 = 67%), while the AFib incidence rate was 0.9%/year (95% CI 0.1–2.4%/year, I 2 = 92%). A longer follow-up duration significantly related to the reduced incidence rate of AFib ( P = 0.02). History of AFib (hazard ratio 11.2, 95% CI 5.9–21.3) and early postoperative AFib (hazard ratio 10.3, 95% CI 5.9–18.0) emerged, instead, as relevant predictors of AFib occurrence. Conclusion: Late atrial arrhythmia occurrence is not infrequent in lung transplantation patients; however, late Afib incidence was rare and showed a time-dependent decrease, particularly in DLT patients, suggesting that a transmural pulmonary veins isolation, the mainstay of transcatheter ablation, is effective in decreasing the likelihood of experiencing AFib. Abstract : Supplemental Digital Content is available in the text